Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\left(x+2\right)\left(x^2-2x+4\right)-\left(x^3-2\right)\)
\(\Rightarrow A=\left(x^3+8\right)-\left(x^3-2\right)\)
\(\Rightarrow A=x^3+8-x^3+2\)
\(\Rightarrow A=\left(x^3-x^3\right)+\left(8+2\right)\)
\(\Rightarrow A=10\)
\(A=\left(x+2\right)\left(x^2-2x+4\right)-\left(x^3-2\right)\)
\(=x^3+8-x^3+2\)
\(=10\)
\(B=\left(x+2\right)\left(x-2\right)\left(x^2+2x+4\right)\left(x^2-2x+4\right)\)
\(=\left(x+2\right)\left(x^2-2x+4\right)\left(x-2\right)\left(x^2+2x+4\right)\)
\(=\left(x^3+8\right)\left(x^3-8\right)\)
\(=x^6-64\)
\(C=\left(x^2+3x+1\right)^2+\left(3x-1\right)^2-2\left(x^2+3x+1\right)\left(3x-1\right)\)
\(=\left(x^2+3x+1\right)^2-2\left(x^2+3x+1\right)\left(3x-1\right)+\left(3x-1\right)^2\)
\(=\left(x^2+3x+1-3x+1\right)^2\)
\(=\left(x^2+2\right)^2\)
\(D=\left(3x^3+3x+1\right)\left(3x^3-3x+1\right)-\left(3x^3+1\right)^2\)
\(=\left(3x^3+1+3x\right)\left(3x^3+1-3x\right)-\left(3x^3+1\right)^2\)
\(=\left(3x^3+1\right)^2-9x^2-\left(3x^3+1\right)^2\)
\(=-9x^2\)
\(E=\left(2x^2+2x+1\right)\left(2x^2-2x+1\right)-\left(2x^2+1\right)^2\)
\(=\left(2x^2+1+2x\right)\left(2x^2+1-2x\right)-\left(2x^2+1\right)^2\)
\(=\left(2x^2+1\right)^2-4x^2-\left(2x^2+1\right)^2\)
\(=-4x^2\)
a) \(=\left(x^2+3x+1\right)^2-2\left(x^2+3x+1\right)\left(3x-1\right)+\left(3x-1\right)^2\)
\(=\left(x^2+3x+1-3x+1\right)^2\)
\(=\left(x^2+2\right)^2\)
b) \(=\left[\left(3x^3+1\right)^2-\left(3x\right)^2\right]-\left(3x^2+1\right)^2\)
\(=-\left(3x\right)^2=9x^2\)
c)\(=\left[\left(2x^2+1\right)^2-\left(2x\right)^2\right]-\left(2x^2+1\right)^2\)
\(=-\left(2x\right)^2=4x^2\)
Bài 1:
a: =>9x^2-6x+1=9x^2-2x
=>-4x=-1
=>x=1/4
b: \(\Leftrightarrow x^2+6x+9-x^2-2x-3=14\)
=>4x+6=14
=>4x=8
=>x=2
Bài 2:
a: \(=2x^2-6x+x-3-x^2+5x+3x=x^2+3x-3\)
b: =x^3-6x^2+12x-8-x^3+6x^2
=12x-8
a, (x4-2x3+2x-1):(x2-1) = \(\frac{\left(x^4-1\right)-\left(2x^3-2x\right)}{x^2-1}\)
= \(\frac{\left(x^2-1\right)\left(x^2+1\right)-2x\left(x^2-1\right)}{x^2-1}\) =\(\frac{\left(x^2-1\right)\left(x^2+1-2x\right)}{x^2-1}\)
= \(x^2+1-2x\)= \(\left(x-1\right)^2\)
b, (8x3-6x2-5x+3):((4x+3)
\(x^3+3x^2+3x+1=\left(x+1\right)^3\)
a) x3 + 3x2 + 3x + 1
= x3 + 3.x2.1 + 3.x.12 + 13
= (x+1)3